The Relationship Between Nutritional Status and History of LBW on Child Development - Khaera, Ummul; Gama, Arlina Wiyata; Larasati, Iip; Rahman, Abd; Pababbari, Musafir (Newinera Publisher, 2025)
Optimal child development reflects the future of a nation. Malnutrition and low birth weight (LBW) history are significant determinants impacting children’s development, especially in low-income settings. This study examines the relationship between nutritional status and LBW history with the development of 4-year-old children using the Developmental Pre-Screening Questionnaire (KPSP). The aim is to identify the relationship between nutritional status and LBW history with the developmental outcomes of children aged 4 years. An observational analytic study with a cross-sectional design was conducted in the working area of Jongaya Health Center, Makassar. The study included 56 children, divided into groups based on their nutritional status and LBW history. Data were collected using anthropometric measurements and KPSP. Statistical analysis was performed to determine significant relationships. The results showed a significant relationship between nutritional status and child development (p<0.05). Additionally, children with LBW history showed delayed development compared to those without LBW history (p<0.05). It concludes that nutritional status and LBW history significantly influence the developmental outcomes of 4-year-old children. Early interventions addressing malnutrition and LBW are crucial to ensure optimal development.